Hormonal profiles of captive Galapagos tortoises (Chelonoidis nigra). Issue 3 (11th March 2016) - Branson, Maile A.; Atkinson, Shannon; Ramos, Meg Ferrell
Abstract : Monthly blood samples, daily mating observations from Galapagos tortoises ( Chelonoidis nigra ), and local rainfall and temperature were collected at the Honolulu Zoo as part of a fertility evaluation. Testosterone concentrations were measured for males ( n = 6), two of which were seen copulating and were considered sexually active. Estrone sulfate and progesterone concentrations were measured for female tortoises ( n = 9), two of which nested and only one had laid eggs. Testosterone profiles were similar for both sexually active and sexually inactive males, both of which were positively correlated with temperature but not rainfall. Peak testosterone concentrations (12.0 ± 1.4 ng/ml sexually active animals vs. 14.4 ± 2.4 ng/ml sexually inactive animals) occurred at the end of the nesting season, from April to July. Estrone sulfate concentrations were similar for nesting ( n = 2) and non‐nesting ( n = 7) female tortoises, rising from non‐detectable concentrations (September), and increasing to peak concentrations during the nesting season. Progesterone concentrations remained low and spiked (9.44 ng/ml) only for the female that nested and laid eggs. Testosterone was negatively correlated with mating behavior, and the male tortoises were likely capable of spermatogenesis even though only two of them engaged in mating behavior. The female tortoises were not senescent, as the estrone sulfate concentrations likely reflected waves of ovarian follicular activity. Endocrine parameters were not in synchrony with rainfall, and a disconnect between the timing of reproductive events and the environmental milieu may help to explain the poor fertility of these tortoises. Zoo Biol. 35:237–245, 2016. © 2016 Wiley Periodicals, Inc.